One new species of Mycterothrips (Thysanoptera: Thripidae) from southern Iran - Alichi, Mahmood; Minaei, Kambiz (Zootaxa, 2019)
The genus Mycterothrips, with 36 species worldwide, is primarily Holarctic, but with several species occurring in the Old World tropics including Australia and Africa (ThripsWiki 2019). The species apparently all feed and breed on leaves, although adults can disperse widely onto many plants. An identification key to 27 species was provided (Masumoto & Okajima 2006), but seven further species were subsequently described from Iran (Mirab-balou et al. 2011; Alavi et al. 2013; Minaei et al. 2017) and a key for distinguishing nine species from this country was presented by Alavi et al. (2013). Recently two further new species were described from tea plants together with a key for 10 species in China (Li et al. 2017).